Digitalisasi Ukm Dalam Hadapi Era Less Contact Economy Pada Masa Covid-19 - Alwendi, Alwendi (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The craft of marine wood waste has been practiced for almost 10 years by the UKM Fortuna Handycraf whose products have been exported to various countries in Europe and America. However, during a pandemic, SMEs find it difficult to increase productivity due to various constraints such as constraints on production technology, marketing and managerial capacity. The Indonesia Bangkit UKM Program provides solutions to overcome these problems, namely solutions to technological capacity constraints by procuring production machines such as cutting machines, sitting drilling machines, compressor machines, work tables and wheelbarrows. Solution to marketing / distribution and managerial constraints by designing and manufacturing an Android-based Management Information System (SIMBA) (inventory management based on online purchase orders), and assist in the preparation of the company's income statement. Besides that, it also offers marketing media using neon box boards. The solutions provided can help increase the productivity of the Fortuna Handycraft SME in terms of production, digital marketing and managerial